2020
DOI: 10.18509/gbp.2020.84
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Socio-Economic Impacts of Photovoltaic Parks in the Centre Development Region. Romania

Abstract: Increasing the share of renewable energy has become one of the key actions Romania has assumed under the Europe 2020 strategy targets on climate change and energy (a.k.a. European 20-20-20 targets). Romania benefits from a wide variety of renewable energy sources (RES) -wind, solar, hydro, geothermal and biomass. Among the RES types, solar resources have started to significantly contribute to the electricity mix. Thus, under the rapid transformation and growth of the renewable energy sector, understanding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…However, our analysis revealed that 80% were installed at least 500 m from the trees to avoid shading and, consequently, decrease the return on the investment. The main socio-economic impacts of the PV parks that could be assessed using the indicator-based analysis are: distance to roads and settlements, hitherto considered as environmental impacts [5,6,7,14], here considered as supporting infrastructure for the economic investment; land/cover changes and the loss of farmland; and solar electric footprint. The network of national and county roads facilitates the access to areas suitable for the construction of photovoltaic parks; most of investments were built so as to benefit from the existing access roads [5,11,6,7].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, our analysis revealed that 80% were installed at least 500 m from the trees to avoid shading and, consequently, decrease the return on the investment. The main socio-economic impacts of the PV parks that could be assessed using the indicator-based analysis are: distance to roads and settlements, hitherto considered as environmental impacts [5,6,7,14], here considered as supporting infrastructure for the economic investment; land/cover changes and the loss of farmland; and solar electric footprint. The network of national and county roads facilitates the access to areas suitable for the construction of photovoltaic parks; most of investments were built so as to benefit from the existing access roads [5,11,6,7].…”
Section: Resultsmentioning
confidence: 99%
“…The main socio-economic impacts of the PV parks that could be assessed using the indicator-based analysis are: distance to roads and settlements, hitherto considered as environmental impacts [5,6,7,14], here considered as supporting infrastructure for the economic investment; land/cover changes and the loss of farmland; and solar electric footprint. The network of national and county roads facilitates the access to areas suitable for the construction of photovoltaic parks; most of investments were built so as to benefit from the existing access roads [5,11,6,7]. For this reason, over 66% of investments in the NWDR are located less than 1 km from roads, which reduces the costs (fast transportation, easy access of the equipment, less and/or no additional investments related to roads).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations